Inside sport psychology - Karageorghis, Costas I. 1969-; Terry, Peter C. 1952- (Human Kinetics, 2011)
With Inside Sport Psychology, you'll discover the relationship between mind, body, and performance. Learn about the techniques that have proven successful for today's top athletes and teams and how you can adapt and apply them in both training and competition. In this essential guide, renowned sport psychologists Costas Karageorghis and Peter Terry explain how to elevate performance through the application of evidence-based strategies and techniques such as these Goal setting Reward strategies Visualization Self-hypnosis Managing anxiety Improving motivation and performance with the use of music Inside Sport Psychology explains psychological principles associated with over 20 sports, including soccer, rugby, tennis, golf, shooting, and track and field. You'll also find tips for managing mood fluctuations, developing confidence, and maintaining consistent performance at every level of competition. With Inside Sport Psychology, you'll go from competitor to champion!